Analysis of the Character Value of "Padusan Tradition" in Pengging Banyudono District, Boyolali Regency - Vilvijaya, Suyahman (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to describe the character values contained in the "tradition of padusan" in the Pengging bath in Banyudono Subdistrict, Boyolali Regency. This research includes qualitative research with a descriptive approach. The subjects of this study were the perpetrators of "traditional padusan" and street vendors around the Pengging bathing area, the object of the research was; character value and 'padusan tradition'. Data collection methods: observation, interviews and documentation. To find out the validity of the data, data triangulation and methods are used. Data analysis techniques using interactive analysis techniques consisting of 3 stages: data reduction, data display and data verification. The results of the study: based on the observations in the field that researchers did since May 2018 found the following: the padusan tradition is carried out every year, the implementation of padusan tradition 2 days before the fasting month, the padusan starting from children to adults, there is entertainment dangdut music with famous singers, ticket prices rose 100%, many traders around the padusan area in Pengging baths, parking of motorbikes and cars doubled with parking wages increasing by 50%, crowded atmosphere of padusan, discipline in the padusan participants dress modestly and neatly, the padusan participants cannot bring and consume, drugs, alcohol, the participants can choose the available swimming pool there are 4 swimming pool choices, and the padusan participants cannot do rituals. The results of interviews with the Padusan tradition actors were found as follows; the reason for joining the padusan is simply to follow in the footsteps of his friends, siblings and family, the purpose of following padusan to be clean and to practice fasting, follow the padusan looking for entertainment, following the padusan filling his spare time, following the padusan preserving the value of local wisdom, following the preservation customs. Interviews with the expert interpreters and street vendors obtained information that the “Padusan Tradition”: bring income, padusan tradition fosters awareness, help help and work together with others, the padusan tradition encourages closeness to God Almighty. The conclusion: that the “padusan tradition” contains many character values including; religious, discipline, mutual cooperation, help.